Poly(ethylene oxide) Functionalized Graphene Nanoribbons with Excellent Solution Processability - Huang, Yinjuan; Mai, Yiyong; Beser, Uliana; Teyssandier, Joan; Velpula, Gangamallaiah; Van Gorp, Hans; Straaso, Lasse Arnt; Hansen, Michael Ryan; Rizzo, Daniele; Casiraghi, Cinzia; Yang, Rong; Zhang, Guangyu; et al. (Journal of the American Chemical Society, 2016)
Structurally well-defined graphene nanoribbons (GNRs) have attracted great interest as next-generation semiconductor materials. The functionalization of GNRs with polymeric side chains, which can widely broaden GNR-related studies on physiochemical properties and potential applications, has remained unexplored. Here, we demonstrate the bottom-up solution synthesis of defect-free GNRs grafted with flexible poly(ethylene oxide) (PEO) chains. The GNR backbones possess an armchair edge structure with a width of 1.0-1.7 nm and mean lengths of 15-60 nm, enabling near-infrared absorption and a low bandgap of 1.3 eV. Remarkably, the PEO grafting renders the GNRs superb dispersibility in common organic solvents, with a record concentration of ∼1 mg mL-1 (for GNR backbone) that is much higher than that (<0.01 mg mL-1) of reported GNRs. Moreover, the PEO-functionalized GNRs can be readily dispersed in water, accompanying with supramolecular helical nanowire formation. Scanning probe microscopy reveals raft-like self-assembled monolayers of uniform GNRs on graphite substrates. Thin-film-based field-effect transistors (FETs) of the GNRs exhibit a high carrier mobility of ∼0.3 cm2 V-1 s-1, manifesting promising application of the polymer-functionalized GNRs in electronic devices.
CRIS-Team Scopus Importer:2023-03-20